Из Именного указателя к «Записным книжкам» Ахматовой: Итальянцы [From an Index to Anna Akhmatova’s _Notebooks_: Italians] - Timenchik, Roman (Slavica Revalensia, 2021)
This article is yet another installment in the series of Roman Timenchik’s annotations to Anna Akhmatova’s Notebooks (see also three previous volumes of Slavica Revalensia). This particular installment concerns two Italians mentioned in Akhmatova’s notes: Bruno Carnevali (1924—1990) and Carlo Riccio (1932—2011).